Reading minds : how childhood teaches us to understand people - Wellman, Henry M.; Lind, Karen (New York : Oxford University Press, 2020)
The need to understand human social life is basic to our human nature and fuels a life-long quest that we begin in early childhood. Key to this quest is trying to fathom our inner mental states--our hopes, plans, wants, thoughts, and emotions. Scientists deem this developing a "theory of mind." In Reading Minds, Henry Wellman tells the story of our journey into that understanding. Our hard-won, everyday comprehension of people and minds is not spoon-fed or taught. Each of us creates a wide-ranging theory of mind step-by-step and uses it to understand how all people work. Failure to learn these steps cripples a child, and ultimately an adult, in areas as diverse as interacting socially, creating a coherent life story, enjoying drama and movies, and living on one's own. Progressing along these steps--as most of us do--allows us to see the nature of our shared humanity, to understand our children and our childhood selves, to teach and to learn from others, and to better navigate and make sense of our social world. Theory of mind is basic to why some of us become religious believers and others atheists, why some of us become novelists and all of us love stories, why some love scary movies and some hate them. Reading Minds illuminates how we develop this theory of mind as children, how that defines us as individuals, and ultimately how it defines us as human.
Reading minds 101 -- Mind reading, gossip, and liars -- Friends, secrets, and lies -- Imagination and reality -- Rutting the theory in theory of mind -- Block by block -- The baby boom: where reading minds begin -- Superpowers, god, omniscience, and afterlife -- Possible worlds, possible minds -- Chimps, dogs, and us: the evolution of reading minds -- The social brain -- Hi, Robert -- Theory of mind at work -- Stories, theories, minds.
Includes bibliographical references (pages [165]-179) and index.
Keywords: Social interaction; Social skills; Social interaction in children; Social skills in children; Philosophy of mind; Philosophy of mind; Social interaction; Social interaction in children; Social skills; Social skills in children; Sozialisation; Interaktion; Sozialkompetenz